2020
DOI: 10.3390/ijerph17062042
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Aerobic Exercise on Depression-Like Behaviors in Chronic Unpredictable Mild Stress Mice and Related Factors in the AMPK/PGC-1α Pathway

Abstract: This study was to study the impact of aerobic exercises on the chronic unpredictable mild stress (CUMS) in mice, and to discuss the possible mechanism from the skeletal muscle AMPK/PGC-1α energy metabolism signaling pathway. The healthy male mice were randomly divided into Control Group (CG), Model Group (MG), and Model Exercise Group (ME).Twelve stress methods were adopted for four weeks (28 days) to establish the depression model. ME was subject to aerobic training plan after the model was established. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Importantly, the correlation analysis results in this study indicate a negative relationship between thermogenic gene expression and physiological and oxidative stress (Table 3 and Figure 6). Physiological stress reduces ATP, increases the ATP/AMP ratio, and activates AMPK, thereby inhibiting PGC-1α expression [72]. It also causes metabolic disorders and lowers immunity [73], and is a risk factor for increased disease and a cause for exercise maladaptations [74].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the correlation analysis results in this study indicate a negative relationship between thermogenic gene expression and physiological and oxidative stress (Table 3 and Figure 6). Physiological stress reduces ATP, increases the ATP/AMP ratio, and activates AMPK, thereby inhibiting PGC-1α expression [72]. It also causes metabolic disorders and lowers immunity [73], and is a risk factor for increased disease and a cause for exercise maladaptations [74].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that AE improved depression-like behaviors or depressive symptoms in CUMS animal models [ 4 , 11 , 36 ]. Ryan et al [ 37 ] found that an 8-week moderate-intensity aerobic exercise training intervention reduced depressive symptoms among individuals with major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, studies have shown favorable effects of exercise on the treatment and rehabilitation of mental and cerebral diseases [ 7 , 8 , 9 ], considering exercise as a nonpharmacological and efficacious approach for the prevention and management of depression [ 4 , 8 , 10 ]. There have been many pieces of research on anti-depression effects of exercise in recent years; however, underlying mechanisms remain obscure [ 7 , 8 , 11 , 12 ]. Previous studies showed that aerobic exercise (AE) could stimulate neuron regeneration, regulate neurotrophin such as brain-derived neurotrophic factor (BDNF) and improve the plasticity of the brain [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations